Mechanical properties and internal microdefects evolution of carbon fiber reinforced polymer composites: Cryogenic temperature and thermocycling effects. (3rd May 2020) - Meng, Jinxin; Wang, Yong; Yang, Haiyang; Wang, Panding; Lei, Qin; Shi, Hanqiao; Lei, Hongshuai; Fang, Daining
Abstract: Carbon fiber reinforced polymer (CFRP) composites with remarkable mechanical properties are widely used in aerospace crafts as load-bearing components. However, harsh environmental conditions challenge the security design of lightweight composite structures. In this work, the effects of cryogenic temperature from 77 K to 298 K and cryogenic stability after 50, 100 and 150 cycles on the mechanical properties and failure modes of CFRP laminates with various stacking sequences were experimentally investigated. In-situ static tensile and three-point bending tests were conducted. A progressive damage model was developed based on three-dimensional (3D) Hashin criterion. Unique insights into the internal microdefect and damage evolution of laminates after 150 thermocycling were obtained by X-ray computed tomography (X-ray CT) technique. The results revealed significant degradation in tensile strength and modulus of laminates with the decrease in temperature due to changes in failure mode. The flexural properties improved by over 50% thanks to shrinkage in chemical bonding between matrix molecules. The influence of thermocycling on the mechanical properties was shown insignificant (0.2%–13%) under slow cooling rates. The degradation in properties of quasi-isotropy laminates looked more significant than that of unidirectional due to the coupling effect of thermal expanding mismatch between material (fiber and matrix) and layer. Quasi-isotropy laminated exhibited significantly greater microcrack volume fractions (more than 6-fold after 150 cycles). As thermocycling rose, the microcracks gradually expanded and nucleation occurred within the interfacial layer. The results here provide a way for the structure design of cryogenic composite tanks under complex working environments by studying the temperature effect. Highlights: In-situ tensile and bending tests are conducted under cryogenic temperatures. A progressive damage model is developed by taking into account temperature effect. Internal microdefect evolution after cryogenic cycling is captured using μ-CT. Failure modes of CFRP laminates with various stacking sequences are discussed.